Pelvic fractures. Issue 6 (June 2021) - Baker, Gavin; Diamond, Owen
Abstract: Pelvic injuries have been increasing in incidence over the past 30 years carrying with them a significant risk of morbidity and also mortality. Patient survival from these injuries is increasing due to improved standards of care both pre-hospital and in hospital. They tend to occur in two distinct populations: young patients in high-energy road traffic collisions and older patients in low-energy injuries. Differentiating those that can be treated conservatively from those that would benefit from surgical stabilization, is based upon good clinical examination, appropriate radiological investigations and knowledge of classification systems. Stabilization for these patients may allow for earlier mobilization and less pain. In displaced or unstable injuries, surgical stabilization is essential to reduce and prevent mal-union, which is associated with poor patient outcome. Due to the significant bony displacement at the time of injury, the severe soft tissue injuries that accompany the bony injuries are often associated with non/mal-union and neurological and urogenital injuries. High-energy pelvic injuries often have significant associated injures and are at high risk of chronic pain and disability; thus they present a significant challenge and hence are best cared for in specialist centres, with a multi-disciplinary team approach.